Large-scale housing projects in Lisbon - Ana Tostões; Zara Ferreira (Docomomo Journal, 2021)
The neighborhoods of Olivais Norte (1960), Olivais Sul (1963) and Telheiras Sul (1974) are paradigmatic examples of the Portuguese State’s response to the housing shortage that was acknowledged in Lisbon, in the period of the post-WWII. Featuring a varied catalogue of architectural trends, this series of projects demonstrated extensive structural, formal, and spatial experimentation that revealed the concerns and quest by their designers to respond to the need for “housing for the greatest number”. What all three projects shared was that they were large scale, publicly financed, started out with similar programs, and that various architectural teams were involved in each of them. The fact that they succeeded one another chronologically enables a critical reading to be made of the evolving interpretation of the Modern Movement in Lisbon, and the pursuit of modernity as an attitude that valued universality, rationality, and a fair response to new social orders.